Impact of heavy ion energy and species on single-event upset in commercial floating gate cells. (May 2021) - Ye, Bing; Mo, Li-Hua; Zhai, Peng-Fei; Cai, Li; Liu, Tao; Yin, Ya-Nan; Sun, You-Mei; Liu, Jie
Abstract: The impact of heavy ion energy and species on single-event upsets (SEU) sensitivity in state-of-the-art NAND Flash memories is investigated in this paper. Experimental results indicate that the heavy ion with the same linear-energy-transfer (LET) but higher energy and mass will cause a decrease in the SEU cross-section of the three kinds of floating gate cells when the device surface LET value is 37.6 and 50.3 MeV ·cm 2 /mg. The Geant4 simulation analysis show that the influence of the sensitive layer depth on LET and the difference in ion track structure are the main mechanisms for this experimental result. Some typical satellite orbits are also selected to study the influence of heavy ion energy and species on predicting the on-orbit error rate using SPACE RADIATION software. Highlights: Experiments and simulations are carried out on SEU of flash memories caused by ions with different energies but same LET. The SEU cross-section caused by high-energy ions is higher in the low LET region, but lower in the high LET region. The ion track structure and the SV layer depth are the dominant factors in the low and high LET regions, respectively.